Determine the impact of market-orientated skill training on satisfaction and effectiveness of trainees in technical and vocational training: A case study in Western Azarbaijan province, Iran - Hassan Nalbandi; S. Jafar Zonoozi (Dutch Journal of Finance and Management, 2019)
The aim of this study was to determine the impact of market-orientated skill training on satisfaction and effectiveness of trainees in technical and vocational training, Western Azarbaijan province, Iran. The population was all trained trainees (700 individuals) of market-oriented courses in the department of technical and vocational training in Western Azerbaijan during 2015/03/21 to 2015/08/23. According to Morgan table, 250 individuals were randomly selected. A designed questionnaire by researcher was used to collect data. Data were analyzed using path analysis. The results revealed that skill training of market orientation had no significant effect on satisfaction and effectiveness of technical and vocational training, Western Azarbaijan province, Iran.
Keywords: 650; market-orientated; skill training; technical and vocational training; satisfaction